2012
DOI: 10.2134/jeq2011.0207
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Pyrolyzed at Two Temperatures Affects Escherichia coli Transport through a Sandy Soil

Abstract: The incorporation of biochar into soils has been proposed as a means to sequester carbon from the atmosphere. An added environmental benefit is that biochar has also been shown to increase soil retention of nutrients, heavy metals, and pesticides. The goal of this study was to evaluate whether biochar amendments affect the transport of Escherichia coli through a water-saturated soil. We looked at the transport of three E. coli isolates through 10-cm columns packed with a fine sandy soil amended with 2 or 10% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 47 publications
5
42
0
Order By: Relevance
“…The authors reported that both high-temperature biochars reduced E. coli transport at the 2 % application rate, with substantially greater reductions observed with the pine chip biochar. Application of the low-temperature poultry litter biochar either had no significant effect or increased transport of both E. coli isolatesresults consistent with those discussed above [10]. Changes in transport behavior following biochar addition were quantitatively similar for both saturated and unsaturated soils, but for all treatments, the effect was more pronounced in partially saturated columns.…”
Section: Biochar Impact On Pathogen Transport and Microbial Propertiessupporting
confidence: 83%
See 2 more Smart Citations
“…The authors reported that both high-temperature biochars reduced E. coli transport at the 2 % application rate, with substantially greater reductions observed with the pine chip biochar. Application of the low-temperature poultry litter biochar either had no significant effect or increased transport of both E. coli isolatesresults consistent with those discussed above [10]. Changes in transport behavior following biochar addition were quantitatively similar for both saturated and unsaturated soils, but for all treatments, the effect was more pronounced in partially saturated columns.…”
Section: Biochar Impact On Pathogen Transport and Microbial Propertiessupporting
confidence: 83%
“…One mode of human exposure to these pathogens is through consumption of fecal contaminated groundwater [63,64]. Transport of microbial pathogens into ground water sources may be significantly reduced by application of biochar [9,10]. Those researchers evaluated transport of three different E. coli isolates through laboratory column that were packed with a fine sandytextured soil and then amended with poultry litter biochar produced at two different pyrolysis temperatures (350 or 700°C).…”
Section: Biochar Impact On Pathogen Transport and Microbial Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil sampling for presence of E. coli O157:H7 by surface plating Soil was tested for presence and populations of E. coli O157:H7 on day 1 (week 0) as well as at the following storage times: weeks 1, 2, 4, 5, 6, 7, and 8 by cultural sampling methods, as modified from previous studies Bolster et al, 2012;Gurtler et al, 2013). At each sampling time, containers were vigorously mixed for 60 s, 1 g was removed from the container, added to 9 mL TSBN, and vortexed thoroughly.…”
Section: Inoculation Of Soilmentioning
confidence: 99%
“…Proteobacteria are a phylum containing many foodborne pathogenic microorganisms such as Salmonella, E. coli O157:H7, Shigella, and Vibrio. Others have noted a decrease in Proteobacteria in biochar-amended soils (Anderson et al, 2011), or have investigated effects of biochar on E. coli transport through soils Bolster et al, 2012). Further work is needed to determine effects of biochar on individual pathogens, such as E. coli O157:H7.…”
Section: Introductionmentioning
confidence: 99%